Real-Time Tumor-Tracking Radiotherapy and General Stereotactic Body Radiotherapy for Adrenal Metastasis in Patients With Oligometastasis. (5th November 2018) - Katoh, Norio; Onishi, Hiroshi; Uchinami, Yusuke; Inoue, Tetsuya; Kuriyama, Kengo; Nishioka, Kentaro; Shimizu, Shinichi; Komiyama, Takafumi; Miyamoto, Naoki; Shirato, Hiroki
Background: Precise local radiotherapy for adrenal metastasis can prolong the useful life of patients with oligometastasis. The aim of this retrospective, 2-center study was to establish the safety and effectiveness of real-time tumor-tracking radiotherapy and general stereotactic body radiotherapy in treating patients with adrenal metastatic tumors. Materials and Methods: Thirteen lesions in 12 patients were treated with real-time tumor-tracking radiotherapy (48 Gy in 8 fractions over 2 weeks) and 8 lesions in 8 patients were treated with general stereotactic body radiotherapy (40-50 Gy in 5-8 fractions over 2 weeks or 60-70 Gy in 10 fractions over 2 weeks). Overall survival rates, local control rates, and adverse effects were analyzed. Results: The actuarial overall survival rates for all patients at 1 and 2 years were 78.5% and 45.8%, respectively, with a median follow-up of 17.5 months, and the actuarial local control rates for all tumors at 1 and 2 years were 91.7% and 53.0%, respectively, with a median follow-up of 9 months. A complete local tumor response was obtained in 3 tumors treated by real-time tumor-tracking radiotherapy (lung adenocarcinomas with diameters of 35, 40, and 60 mm). There was a statistically significant difference in the local control between the groups treated by real-time tumor-tracking radiotherapy (100% at 1 year) and general stereotactic body radiotherapy (50% at 1 year; P < .001). No late adverse reactions at Grade 2 or higher were reported for either treatment group. Conclusions: This study showed that although both treatments are safe and effective, the real-time tumor-tracking radiotherapy is more effective than general stereotactic body radiotherapy in local control for adrenal metastasis.